PENGGUNAAN METODE DRILL UNTUK MENINGKATKAN KEMAMPUAN MENGGAMBAR PESERTA DIDIK PADA MATA PELAJARAN SENI BUDAYA KELAS VII.1 MTs PSA SULIT AIR TAHUN 2014 - M U L Y A D I, Drs. Suib Awrus, M.Pd, Drs. Abd. Hafiz,M.Pd (Serupa The Journal of Art Education, 2014)
This Research is purpose to know 1) ability drawing to learners with usage drill method (partice) 2) How big increase valae of draw with usage drill method and to knaw the result of the MTs PSA Sulit Air with usage this methodThis research did in MTs PSA Sulit Air Subdistriet of X Koto Diatas Solok. The researcher fowes in the class of VII.1 cansist 26 person. The Instrument is used to collect data are direct pratice test drawing of learners dan use observati.This research is an action research with stepResult of research indicate that 1) result of ability draw educative participant at cycle of I average ( 76,61) 2) result of ability of educative participant at cycle of II average ( 85,79), result of ability value draw progressively mount from cycle, cycle of I, up to cycle of II seen at result of value draw which is obtained by educative participant progressively mount, and also educative participant activity in study progressively mountResult of research can be concluded that passing method of drill can improve ability participant in draw signifikanKeyword : Drawing, Ability, Drill ( practice)